A free and fair economy: A game of justice and inclusion - Ghislain-Herman Demeze-Jouatsa; Roland Pongou; Jean-Baptiste Tondji (Bielefeld University, Center for Mathematical Economics (IMW), 2021)
Frequent violations of fair principles in real-life settings raise the fundamental question of whether such principles can guarantee the existence of a self-enforcing equilibrium in a free economy. We show that elementary principles of distributive justice guarantee that a pure-strategy Nash equilibrium exists in a finite economy where agents freely (and non-cooperatively) choose their inputs and derive utility from their pay. Chief among these principles is that: 1) your pay should not depend on your name; and 2) a more productive agent should not earn less. When these principles are violated, an equilibrium may not exist. Moreover, we uncover an intuitive condition|technological monotonicity|that guarantees equilibrium uniqueness and efficiency. We generalize our findings to economies with social justice and inclusion, implemented in the form of progressive taxation and redistribution, and guaranteeing a basic income to unproductive agents. Our analysis uncovers a new class of strategic form games by incorporating normative principles into non-cooperative game theory. Our results rely on no particular assumptions, and our setup is entirely non- parametric. Illustrations of the theory include applications to exchange economies, surplus distribution in a firm, contagion and self-enforcing lockdown in a networked economy, and bias in the academic peer-review system.
urn:nbn:de:0070-pub-29574704
Keywords: C72; D30; D63; J71; J38; 330; Market justice; Social justice; Inclusion; Ethics; Discrimination; Self-enforcingcontracts; Fairness in non-cooperative games; Pure strategy Nash equilibrium; Efficiency